Analysis of the Implementation of P5 with Learning Technologies in High Schools: A Case Study Approach - Multazam, Muhammad (Lafadz Jaya Publisher, 2023)
This paper investigates the implementation of P5 (Project-Based Learning) in conjunction with learning technologies in high schools. P5 offers an innovative approach to integrating technology with traditional learning methodologies, promoting student engagement and enhancing problem-solving skills. By analyzing current practices within various high schools, this study explores the benefits, challenges, and outcomes associated with the integration of technology in P5 projects. The study employs a mixed-methods approach, combining quantitative surveys with qualitative interviews from students and teachers. Findings reveal that while P5 facilitates active learning and critical thinking, challenges such as resource limitations, teacher readiness, and technological infrastructure remain significant barriers. The paper concludes by proposing strategies for effective implementation and scaling of P5 in diverse educational contexts.